Work Posture and Musculoskeletal Disorders of Tempe Craftsmen in Sanan Tempe Industrial Center, Malang East Java, Indonesia - Wuri Ayu Wirdhani; Rudi Wibowo; Ancah Caesarina Novi (Humanistic Network for Science and Technology (HNST), 2019)
Musculoskeletal disorders is an uncomfort symptom in the muscles and bones area. It start from very mild to very severe and often due to repeatedly heavy burden that received for long period. Musculoskeletal disorders in workers become an important problem because it can cause lost work time, decrease in work productivity, decrease alertness, increase the risk of accidents, and high handling costs. In tempe industry, soybeen usually washed in manual procedure and this process often causes pain in the waist, spine, and both hands of the workers. Manual soybean washing can cause working accidents and work-related illnesses. Manual soybean washing are involving muscles and bones that have damage potency to the spine. The purpose of this study was to analyze the relationship between work posture and musculoskeletal disorders in Sanan Tempe Industrian Center, Malang. This study research design was an observational analytic with a cross sectional approach. Based on this study it can be concluded that there is a relationship between work posture and musculoskeletal disorders. The industry should organize training that gain an information and action to reduce the harm potential of wrong work postures on tempe craftsmen. Keywords: Musculoskeletal disorders, Tempe craftsmen, Work posture